Caffeine intake and its influences on heart rate variability recovery in healthy active adults after exercise: A systematic review and meta-analysis - Porto, Andrey Alves [UNESP]; Benjamim, Cicero Jonas R.; Gonzaga, Luana Almeida [UNESP]; Luciano de Almeida, Mariana; Bueno Júnior, Carlos Roberto; Garner, David M. [UNESP]; Valenti, Vitor Engrácia [UNESP] (Elsevier, 2022)
Aims: Results regarding the effects of caffeine (CAF) intake on the autonomic control of heart rate recovery exercise remain inconclusive. Thus far, no study has used effect measures to pool the results of different experiments. We aim to assess the acute effect of CAF intake before exercise on the recovery of heart rate variability (HRV) after exercise through a systematic review and meta-analysis. Data synthesis: Randomized controlled clinical trials were included; sample composed of physically active or trained adults; CAF should be offered/ingested before exercise, with dosage between 100 and 400 mg or between 2 and 6 mg/kg and administration/ingestion route analogous in the protocols; studies required to present results of HRV indices before and after exercise. Bias risk analysis and meta-analysis were performed. Twelve studies were included in the qualitative synthesis and five studies were encompassed in the quantitative synthesis (meta-analysis). For the Root-mean-square standard deviation (RMSSD) index we revealed p = 0.67, Total 95% confidence interval (95% CI) ranged from −0.45 to 0.29, and 66.7% for heterogeneity between groups were reported. Concerning the High Frequency (HF) index, we observed p = 0.22, Total 95% CI that ranged from −0.34 to 0.30, and 44% for heterogeneity between groups. Conclusions: CAF intake did not affect heart rate variability recovery after exercise.
Keywords: Autonomic nervous system; Caffeine; Exercise; Heart rate variability; Post-exercise; Systematic review